The role of non-governmental organizations in policy making: the case of anti-sexual harassment legislation in Egypt - Swailam, Injie (AUC Knowledge Fountain, 2015)
Egypt has recently seen several high profile misfortunate incidents were women and girls were attacked, sexually abused and harassed. This thesis studies the role that NGOs play in impacting anti-sexual harassment legislation in Egypt. It addresses participatory policy making and the complex relationship between state and NGOs.Challenges, concerns and considerations to collaborative work between the two are presented. The study proposes a conceptual framework for the different strategies that NGOs use to influence policy making. The method used is qualitative, through interviews with Egyptian NGOs working on the issue.Collaborative, confrontational, legitimacy building, community representation, advocacy, media engagement, partnerships and program implementation are all strategies that guide the conceptual framework and the study. The thesis argues that the strategies and approaches adopted by NGOs have an effect on their level of involvement in policy making. The main finding of the study is that the more NGOs are working on becoming partners of state and avoiding confrontational strategies that could jeopardize their legitimacy and ability to represent the people, the more they become partners in policy making. NGOs need to be aware of their potential and their ability to bring innovative approaches to becoming part of policy reform. Their relationships with their beneficiaries, state and media can indicate whether or not they are legitimate actors of policy making. Understanding that policy reform is a long complicated process and that there is a gap and lack of trust between government and NGOs, is strategic for the later to identify schemas to overcome this. With recent developments of law modifications and national strategies in Egypt, this study is important to conceptualize strategies and approaches for future endeavors of civil society in policy making.